Jerome, Epistle 106 : (on the Psalms) - Jerome, Saint, -419 or 420; Graves, Michael, 1973-; Jerome, Saint, -419 or 420.; Jerome, Saint, -419 or 420. (Atlanta, SBL Press, 2022)
"In this volume of the Writings from the Greco-Roman World series, Michael Graves offers the first accessible English trnaslation and commentary on Jerome's Epistle 106, an important work of patristic biblical interpretation. In his treatise Jerome discusses different textual and exegetical options according to various Greek and Latin copies of the Psalms with input from the Hebrew. Epistle 106 provides insightful commentary on the Gallican Psalter, Jerome's translation of Origen's hexaplaric edition. Jerome's work offers a unique window into the complex textual state of the Psalter in the late fourth century and serves as an outstanding example of ancient philological scholarship on the Bible. Graves's tanslation and commentary is an essential resource for scholars and students of patristic exegesis, biblical rtextual criticism, and late antiqu Christianity" --page 4 of cover.
Abbreviations -- Introduction: Jerome's life and writings -- Jerome's three translations of the Psalms -- Jerome's Epistle 106 -- The text of the Psalms in Jerome's time -- Textual agreement trends in Epistle 106 -- The authenticity and date of Epistle 106 -- Principles of translation in Epistle 106 -- Textual criticism in Epistle 106 -- Interpreting the Psalms in Epistle 106 -- Text, translation, and notes -- Commentary -- Bibliography: Editions and translations of Epistle 106 -- Biblical texts -- Patristic works -- Other resources and studies -- Ancient sources index -- Modern authors index -- Subject index.
Includes bibliographical references and indexes.
Keywords: Jerome, -- Saint, -- -419 or 420.; Bible. -- Commentaries -- Early works to 1800.